Accumulation and distribution of calcium and magnesium in oat and correlation analysis with the uptake of sodium, potassium, and chloride elements. Issue 22 (16th December 2018) - Han, Lipu; Fu, Tonggang; Liu, Jintong; Yu, Shuhui; Gao, Hui; Eneji, A. Egrinya; Liang, Hongzhu
ABSTRACT: Calcium and magnesium are related to the structure and functions of soil, especially the saline alkali soil. This study aimed to explore calcium element and magnesium element concentration and accumulation in relation to salt ion uptake and soil quality. The two elements in plant organs were studied for six oat varieties at four growth stages. The results showed that calcium element concentration and accumulation across plant organs ranged from 3.4 to 12.1 g kg −1 and 2.6 to 6.3 kg ha −1 while those for magnesium element ranged from 1.7 to 5.3 and 1.5 to 3.3. Among varieties, the concentrations and accumulations varied significantly. Significant variations also occurred among the four growth stages with a peak at delayed harvest stage. However, the highest accumulation occurred at maturity. The ratio [calcium element/magnesium element] increased from elongation (heading stage) (1.2 to 1.9 times) to delayed harvest stage (2.9 to 3.2 times). A significant (partial) positive correlation was found among concentrations of calcium, magnesium, chlorine, potassium elements and sodium. The prospect of using oat treated with calcium and magnesium fertilizer to reduce soil alkalinity should be studied further.